2022
DOI: 10.1088/1402-4896/ac7983
|View full text |Cite
|
Sign up to set email alerts
|

Strained Cs2AgInCl6 double perovskite material: band structure, optical spectra and mechanical stability

Abstract: The optoelectronic properties and mechanical stability of lead-free halide double perovskite, Cs2AgInCl6, with emphasis on their dependence on strain are reported. The computations are performed by employing first-principles calculations within a hybrid functional. The authors’ calculation shows a direct (Г→Г) band gap for unstrained Cs2AgInCl6 with a recorded value of 3.62 eV which accords to within 2% with the experiment. The obtained optical spectra show superior properties with strong absorption spectra of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…[1][2][3][4][5] Perovskite materials are a full of promise classification of materials in photovoltaic and optoelectronic applications. [6][7][8][9][10][11][12][13] This category has scoped the ability of changing the productivity of larger than 25%. Halide perovskites (HPs) account for munitions which are promising for light-emitting (LE) and light-gathering appliances.…”
mentioning
confidence: 99%
“…[1][2][3][4][5] Perovskite materials are a full of promise classification of materials in photovoltaic and optoelectronic applications. [6][7][8][9][10][11][12][13] This category has scoped the ability of changing the productivity of larger than 25%. Halide perovskites (HPs) account for munitions which are promising for light-emitting (LE) and light-gathering appliances.…”
mentioning
confidence: 99%
“…[28] Recently, the exchange-correlation hybrid functional has been successfully applied in the computation of double perovskite materials. [7,[25][26][27][29][30][31][32] It is reported that for perovskite materials, A 2 BX 6 exchange-correlation hybrid functional provides the best possible agreement with the experimental findings. [18,[33][34][35] Basis set LANL2DZ has been applied previously to study the physical and chemical properties of perovskite materials.…”
Section: Computational Detailsmentioning
confidence: 99%
“…In addition to tuning the band gap in the single perovskite, the study of band gap tuning of double perovskite using strain was carried out. The variations in the electronic and optical properties were reported by applying strains ranging from −5% to +5% on the double perovskite Cs 2 AgInCl 6 (CAIC) [32][33][34]. However, the band gap of CAIC is 3.33 eV which is high and makes it unsuitable for photovoltaic applications [35].…”
Section: Introductionmentioning
confidence: 99%